Micronutrients and risks of three main urologic cancers: A mendelian randomization study - Lu, Yi; Su, Hao; Wang, Yutao; Li, Hongjun (Frontiers in Nutrition, 2023)
Background The effect of micronutrients on urologic cancers has been explored in observational studies. We conducted the two-sample mendelian randomization (TSMR) study to investigate whether micronutrients could causally influence the risk of urologic cancers. Methods Summary statistics for four micronutrients and three main urologic cancers outcomes were obtained from genome-wide association studies (GWAS). MR analyses were applied to explore the potential causal association between them. Sensitivity analyses using multiple methods were also conducted. Results Genetically predicted one SD increase in serum copper and iron concentrations was causally associated with increased risks of renal cell carcinoma (RCC) (OR = 3.021, 95%CI = 2.204–4.687, P < 0.001, male; OR = 2.231, 95%CI = 1.524-3.953, P < 0.001, female; OR = 1.595, 95%CI = 1.310–1.758, P = 0.0238, male; OR = 1.484, 95%CI = 1.197–2.337, P = 0.0210, female, respectively) and per SD increase in serum zinc levels was related to decreased risks of RCC (OR = 0.131, 95%CI = 0.0159–0.208, P < 0.001, male; OR = 0.124, 95%CI = 0.0434–0.356, P < 0.001, female). No significant results were observed between micronutrients and the risk of bladder cancer after Bonferroni correction. Additionally, per SD increase in serum zinc level was associated with a 5.8% higher risk of prostate cancer (PCa) [OR = 1.058, 95%CI = 1.002–1.116, P = 0.0403, inverse-variance weight (IVW)]. Conclusions Micronutrients play a vital role in the development of urological tumors. Future studies are required to replicate the findings, explore the underlying mechanisms, and examine the preventive or therapeutic role of micronutrients in clinical settings.